2014
DOI: 10.7166/25-1-663
|View full text |Cite
|
Sign up to set email alerts
|

Microfocus X-Ray Computed Tomography (CT) Analysis Of Laser Sintered Parts

Abstract: Microfocus X-ray computed tomography (CT) scanning is a three-dimensional (3D) nondestructive technique that is useful in many research and technology fields. Similar to twodimensional (2D) X-ray inspections, this 3D technology allows the investigation of almost any material down to 1 micron spatial resolution and higher. In this paper we present a characterisation and demonstration of the use of CT to analyse the 3D volume of laser sintered parts including analyses of porosity, dimensional measurement of crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…13 Some porosity analysis by CT analysis of additive manufactured metals is reported in the study by Becker et al 14 The authors of this present article have reported the methodology for nondestructive testing and qualification of additively manufactured medical implants at various resolutions and scan parameters (du Plessis et al, unpublished material). The general use of X-ray tomography in additive manufactured part inspection has also been reported in the study by du Plessis et al 15 and recently has been shown to also be useful for dimensional accuracy assessment for consumer-grade 3D printing, where the same methodology can be applied to any additive process. 16 Recently, a very flat layered form of defect was reported using X-ray tomography of an additive manufactured test part, which is speculated to be due to improper fusion in one or more layers of powder.…”
Section: Introductionmentioning
confidence: 69%
“…13 Some porosity analysis by CT analysis of additive manufactured metals is reported in the study by Becker et al 14 The authors of this present article have reported the methodology for nondestructive testing and qualification of additively manufactured medical implants at various resolutions and scan parameters (du Plessis et al, unpublished material). The general use of X-ray tomography in additive manufactured part inspection has also been reported in the study by du Plessis et al 15 and recently has been shown to also be useful for dimensional accuracy assessment for consumer-grade 3D printing, where the same methodology can be applied to any additive process. 16 Recently, a very flat layered form of defect was reported using X-ray tomography of an additive manufactured test part, which is speculated to be due to improper fusion in one or more layers of powder.…”
Section: Introductionmentioning
confidence: 69%
“…The samples were subjected to X-ray micro-computed tomography (MicroCT) [14]. MicroCT scans were done with a General Electric Phoenix V|Tome|X L240 system at 160 kV and 200 μA, including beam filtering of 0.5 mm copper; the resolution was 10 μm.…”
Section: X-ray Micro-computed Tomographymentioning
confidence: 99%
“…This requires very high scan quality and advanced software tools to allow sub-voxel precision, something which is not always available and was not available at the Stellenbosch CT facility until 2014. Prior to this, various analyses were possible, but precision was limited to basic edge determination tools as shown in a Rapdasa proceedings paper in [17]. The advanced surface determination is demonstrated on a 10 mm Ti6Al4V cube in Figure 4, showing the 3D interpolation of grey values to determine the exact surface location -with high scan quality this can be as accurate as 1/10 th the voxel size.…”
Section: Densitymentioning
confidence: 99%